Zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in air atmosphere, preparation method of zirconium carbide-based catalytic material and method for degrading sulfur hexafluoride
By using zirconium carbide-based catalytic material and combining silicon carbide as a support, sulfur hexafluoride is efficiently degraded under an air atmosphere, solving the problem of difficult degradation of SF6 at lower temperatures in the prior art, and achieving an efficient and environmentally friendly degradation effect.
Patent Information
- Application Number
- CN202411791167.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to efficiently degrade sulfur hexafluoride (SF6) under air atmosphere, especially at lower temperatures, which lack effective degradation mechanisms and techniques.
Zirconium carbide (ZrC) is used as the center of the active site and silicon carbide (SiC) is used as the support to prepare ZrC-based catalytic material through physical grinding method, which can efficiently degrade sulfur hexafluoride under an air atmosphere.
It achieves efficient degradation of sulfur hexafluoride in an air atmosphere at 500-600°C, with a degradation rate of up to 100%, and is simple in process and low in cost, which is suitable for large-scale production.
Smart Images

Figure CN119588392A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material technology, and in particular to a zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere, a preparation method thereof, and a method for degrading sulfur hexafluoride. Background Art
[0002] In recent years, global warming has brought a series of problems to human sustainable development. Greenhouse gases are the culprit of global warming. Sulfur hexafluoride (SF 6 ) is one of the six greenhouse gases that should be limited in the Kyoto Protocol. It has a high global warming potential (GWP), which is higher than carbon dioxide (CO 2 ) times. In addition, sulfur hexafluoride can remain stable in the atmosphere for 3,200 years. 6 It has excellent inert stability and fire resistance and is widely used in power-off and insulation equipment. 6 Gas equivalent to 125 million tons of CO 2 Gas. With the development of the power system, it is expected that SF 6 The emission of sulfur hexafluoride will continue to increase, which is bound to greatly increase the pressure on environmental protection. Therefore, it is urgent to control the emission of sulfur hexafluoride and find a method to degrade sulfur hexafluoride.
[0003] Zirconium carbide (ZrC), similar to Group IV, V, and VI carbides of other transition metals, exhibits an unusual combination of properties. These carbides combine the cohesive properties of covalently bonded ceramics (high melting point, high strength, and hardness) with the electronic properties of metals (high thermal and electrical conductivity), making them very promising for applications in high-temperature thermocatalysis.
[0004] At present, there are many methods for degrading sulfur hexafluoride, including adsorption, thermal decomposition, photodegradation, plasma and catalytic degradation. Among them, catalytic degradation has received special attention. There are three main types of catalysts for the degradation of sulfur hexafluoride: metal oxides, metal phosphates, and supported metal catalysts. These catalysts are all carried out in an argon or nitrogen atmosphere above 600°C. There is currently a lack of research on the degradation mechanism and technology under lower temperature atmospheric conditions. For example, Zhang Jia et al. (CN103007736A) used electroplating sludge to effectively degrade sulfur hexafluoride, but the degradation process needed to be carried out under a nitrogen protective atmosphere. Under realistic conditions, sulfur hexafluoride is in the atmosphere, and the nitrogen protective atmosphere greatly hinders the degradation of SF 6 Therefore, it is necessary to develop a simple and environmentally friendly catalyst that can degrade SF 6 catalytic materials.
[0005] The Chinese patent application document with publication number CN113244939A discloses a silicon carbide-iron oxide composite material for decomposing sulfur hexafluoride in an atmospheric environment. The composite material is a powder composite material with a heat conductive material as a carrier and iron oxide as the active site center. The mass ratio of the carrier to the iron oxide is 10:1 to 60:1. It can achieve the activation and decomposition of sulfur hexafluoride and can decompose sulfur hexafluoride in an atmospheric environment, which conforms to the actual situation and has great practical potential. The catalytic material is prepared by a simple self-assembly chemical deposition method, which has a simple process and low processing cost and is suitable for large-scale production. However, the above method requires a high temperature of 600°C to SF6. 6 The catalytic material preparation process is complicated and not suitable for industrial production, and the energy consumption for degradation is also high.
[0006] The Chinese patent application document with publication number CN116078416A discloses a manganese-based catalytic material for degrading sulfur hexafluoride in an air atmosphere. The manganese-based catalytic material uses metal manganese as the active site center and uses one or more of silicon carbide, silicon dioxide, rectorite, mullite, and hydrotalcite as a carrier. The manganese-based catalytic material can be used to catalytically degrade sulfur hexafluoride in an air atmosphere. Different from the previous technology that requires degradation in a protective atmosphere of nitrogen or argon, it is very consistent with the actual situation and has great practical potential. It can be prepared by a simple physical grinding method without sintering, has a simple process, low processing cost, and is suitable for large-scale production. However, when the temperature is 500°C, the above-mentioned catalytic material has a high degradation rate on SF6. 6 The highest degradation rate is only 85%, which cannot achieve efficient degradation of SF 6 .
[0007] The Chinese patent application document with publication number CN116474762A discloses a catalytic material based on molybdenum dioxide for degrading sulfur hexafluoride in an air atmosphere. The catalytic material uses molybdenum dioxide as the active site center and one or more of silicon carbide and silicon dioxide as a carrier. The molybdenum dioxide material is used for catalytic degradation of sulfur hexafluoride in an air atmosphere. 2 Based on MoO 2 As the active site center, one or more of silicon carbide and silicon dioxide materials are used as carriers. It can be prepared by a simple physical grinding method, without sintering, with simple process and low processing cost, which is suitable for large-scale production. However, when the temperature is 500°C, the above catalytic materials have no effect on SF 6 The highest degradation rate was only 73.33%, and the unit degradation amount was only 123.42 mL g -1 , it is impossible to achieve efficient degradation of SF 6 . Summary of the invention
[0008] The technical problem to be solved by the present invention is how to efficiently degrade SF in an air atmosphere. 6 .
[0009] The present invention solves the above technical problems through the following technical means:
[0010] A zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere has zirconium carbide as the active site center and silicon carbide as the carrier. The zirconium carbide is dispersed on the silicon carbide, and the mass of the zirconium carbide accounts for 5-50% of the mass of the catalytic material.
[0011] Preferably, the mass of the zirconium carbide accounts for 10% of the mass of the catalytic material.
[0012] The present invention also proposes a method for preparing the zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere, comprising the following steps: physically mixing zirconium carbide and silicon carbide to obtain the zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere.
[0013] Preferably, the physical mixing is carried out by grinding.
[0014] The present invention also proposes an application of the zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere in degrading sulfur hexafluoride.
[0015] The present invention also proposes a method for degrading sulfur hexafluoride using the zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere, comprising the following steps: placing the zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere in a reaction device, introducing a mixed gas of sulfur hexafluoride and air, and performing heating treatment at 500-600° C. to degrade sulfur hexafluoride.
[0016] Preferably, in the mixed gas of sulfur hexafluoride and air, the volume concentration of sulfur hexafluoride is not greater than 60 vol.%.
[0017] Preferably, in the mixed gas of sulfur hexafluoride and air, the volume concentration of sulfur hexafluoride is 10-60 vol.%.
[0018] Preferably, the method further comprises subjecting the heated gas to treatment with a 5 mol / L sodium hydroxide solution.
[0019] Preferably, the heat treatment is performed at 500° C. to degrade sulfur hexafluoride.
[0020] Preferably, the flow rate of the mixed gas of sulfur hexafluoride and air is 10 mL / min.
[0021] Preferably, the heating treatment time is 30-240 min.
[0022] Preferably, the heating treatment time is 30-140 min.
[0023] Preferably, the heating treatment time is 30-110 min.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The ZrC-based catalytic material of the present invention uses ZrC as the active site center and silicon carbide as the carrier. It can be prepared by a simple physical grinding method without sintering, has a simple process, low processing cost, and is suitable for large-scale production.
[0026] (2) The catalytic material of the present invention has excellent degradation ability for sulfur hexafluoride and basically does not produce toxic gas, which is in line with the concept of environmental protection.
[0027] (3) The catalytic material of the present invention can degrade sulfur hexafluoride in an air atmosphere, which is different from the previous technology that requires degradation in a protective atmosphere of nitrogen or argon. It is very consistent with the actual situation and has great practical potential.
[0028] (4) The catalytic material of the present invention has a very rapid response to the degradation of sulfur hexafluoride and a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope image of the ZrC-based catalytic material prepared in Example 1 of the present invention;
[0030] Figure 2 This is a transmission electron microscope energy dispersive X-ray spectroscopy image of the ZrC-based catalytic material prepared in Example 1 of the present invention;
[0031] Figure 3 This is a schematic diagram of a device for catalytic degradation of sulfur hexafluoride according to the present invention;
[0032] Figure 4 The curve showing the change of sulfur hexafluoride degradation efficiency with increasing reaction time of the present invention;
[0033] Figure 5 The influence curve of different compositions of the ZrC-based catalytic material of the present invention on the degradation efficiency of sulfur hexafluoride and the comparison of the degradation amount;
[0034] Figure 6 This is a curve showing the effect of different carriers of the ZrC-based catalytic material of the present invention on the degradation efficiency of sulfur hexafluoride;
[0035] Figure 7 This is the influence curve of different treatment temperatures on the degradation efficiency of sulfur hexafluoride in the present invention;
[0036] Figure 8This is the influence curve of different active centers on the degradation efficiency of sulfur hexafluoride in the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0039] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0040] Example 1
[0041] 1. Preparation of ZrC-based catalytic materials
[0042] ZrC was used as the active center and silicon carbide was used as the carrier. The mass ratio of ZrC in the catalytic material was controlled to be 10wt%. 0.1g ZrC and 0.9g silicon carbide were mixed and ground in a mortar for 20 minutes to obtain a powdered ZrC-based catalytic material.
[0043] Scanning electron microscope images of the prepared ZrC-based catalytic materials, such as Figure 1 Then, the ZrC-based catalytic material was characterized by transmission electron microscopy energy dispersive X-ray spectroscopy, as shown in Figure 2 As shown by Figure 1-2 It can be seen that ZrC is dispersed in the silicon carbide carrier.
[0044] 2. Apparatus for treating sulfur hexafluoride using ZrC-based catalytic materials
[0045] like Figure 3The structure diagram of the device for treating sulfur hexafluoride with ZrC-based catalytic materials is shown, which includes the following components: 1 pure sulfur hexafluoride gas cylinder; 2 gas flow meter; 3 gas mixer; 4 quartz reaction tube; 5 tubular furnace; 6 alkali solution recovery device; 7 gas chromatograph; A air inlet; B reacted gas outlet. Among them: the air in the air inlet A and the sulfur hexafluoride gas in the pure sulfur hexafluoride gas cylinder 1 pass through the gas flow meter 2, enter the gas mixer 3 to be mixed, and then are sent to the quartz reaction tube 4, the quartz reaction tube 4 has a ZrC-based catalytic material built in, the quartz reaction tube 4 is set in the tubular furnace 5, and is heated to the treatment temperature by the tubular furnace 5. The gas treated from the quartz reaction tube 4 is sent to the alkali solution recovery device 6, and the gas treated by 6 enters the gas chromatograph 7 for detection, and is discharged from the reacted gas outlet B.
[0046] 3. A process for treating sulfur hexafluoride with a ZrC-based catalytic material, comprising the following steps:
[0047] (1) Configuration of sulfur hexafluoride waste gas:
[0048] The sulfur hexafluoride waste gas used in the experiment is a mixed gas of sulfur hexafluoride and air in a simulated configuration. In this embodiment, the concentration of sulfur hexafluoride is controlled at 10 vol.% by the gas flow meter 2 and the gas mixer 3.
[0049] (2) The mixed and ground ZrC-based catalytic material is filled into the quartz reaction tube 4, and the mixed gas of sulfur hexafluoride and air is continuously fed into the quartz reaction tube 4 for treatment, with the mixed gas flow rate being 10 mL / min.
[0050] (3) The quartz reaction tube 4 is placed in a tubular furnace 5 and the temperature is controlled at 500° C. The tail gas from the quartz reaction tube 4 is passed into an alkali solution recovery device 6. The gas after tail gas absorption by a 5 mol / L sodium hydroxide solution enters a gas chromatograph 7 for detection and is discharged from a post-reaction gas outlet B directly into the atmosphere.
[0051] Example 2
[0052] The ZrC-based catalytic material preparation method, treatment device and treatment process of Example 1 are used, except that the treatment time after the quartz reaction tube is heated to 500°C is adjusted, and its effect on the degradation efficiency is tested. The results are as follows: Figure 4 shown.
[0053] from Figure 4 It can be seen that when the temperature is 500℃, sulfur hexafluoride has a good degradation efficiency, and the highest degradation rate is 100% (corresponding to the degradation time of 30-110min). In the total degradation time of 0-140min, the SF6 on the unit mass of ZrC 6 The degradation amount was 986.5 mL g -1.
[0054] Example 3
[0055] The ZrC-based catalytic material preparation method, treatment device and treatment process of Example 1 are used, except that the ratio of silicon carbide and ZrC in the ZrC-based catalytic material is adjusted (the mass of the prepared catalytic material is 1 g), as shown in Table 1, and its effect on the degradation efficiency is tested. The results are as follows: Figure 5 shown.
[0056] Table 1. Effects of composition and ratio of different ZrC-based catalytic materials on degradation
[0057] Serial number ZrC mass ratio Highest degradation efficiency <![CDATA[SF degradation amount per unit mass of ZrC 6 > Example 2 10wt% 100% <![CDATA[986.5mL g -1 ]]> Example 3-1 0wt% 0% <![CDATA[0mL g -1 ]]> Example 3-2 5wt% 67.11% <![CDATA[457.0mL g -1 ]]> Example 3-3 50wt% 100% <![CDATA[290.1mL g -1 ]]> Embodiment 3-4 100wt% 26.98% <![CDATA[10.9mL g -1 ]]>
[0058] analyze:
[0059] The mass ratio of ZrC in the catalytic material to SF 6 The degradation effect is greatly affected. When no carrier is added, the maximum degradation rate of pure ZrC material is 26.98%, and the degradation effect is poor, indicating that ZrC has excellent catalytic effect only when ZrC is composited with SiC. The maximum degradation rate of ZrC-based catalytic material with a ZrC loading of 5wt% is 67.11% (degradation time is 10min), and the degradation time of SF per unit mass of ZrC is 24.8%. 6 The degradation amount reached 457.0 mL g -1 , the degradation life is 60 minutes. When the specific gravity of ZrC rises to 10wt%, the maximum degradation rate rises to 100% (degradation time is 30-110min). During the total degradation time, the SF per unit mass of ZrC 6 The degradation amount was 986.5 mL g -1 However, when the ZrC content increases further, SF 6 The degradation effect of ZrC began to decline. When the ZrC content reached 50wt%, the degradation efficiency was 100% within 30-140min. 6 The degradation amount was 986.5 mL g -1 Down to 290.1 mL g -1 . This is because SiC plays the role of electron donor and dispersant in the composite material. On the one hand, the reduction of SiC limits the electron diffusion efficiency and greatly weakens the degradation site of Zr-C; at the same time, the metal oxide fluoride will re-sinter at high temperature, which may cause the contact area to decrease, block the gas flow, and reduce the reaction rate. Therefore, the content of ZrC in the ZrC-based catalytic material is preferably 10wt%.
[0060] Example 4
[0061] The ZrC-based catalytic material preparation method, treatment device and treatment process of Example 1 are used, except that the choice of carrier is adjusted as shown in Table 2, and its effect on the degradation efficiency is tested. The results are as follows: Figure 6 shown.
[0062] Table 2. Effects of different carrier selections on degradation
[0063] Serial number Vector selection Highest degradation efficiency <![CDATA[SF degradation amount per unit mass of ZrC 6 > Example 2 Silicon Carbide 100% <![CDATA[986.5mL g -1 ]]> Example 4-1 Silicon dioxide 43.23% <![CDATA[165.3mL g -1 ]]> Example 4-2 Zirconium Dioxide 16.19% <![CDATA[54.4mL g -1 ]]>
[0064] analyze:
[0065] The selection of different supports will have a great influence on the performance of ZrC-based catalytic materials. 2 When used as a carrier, it degrades SF at 500°C 6 This is because SiO 2 The crystal size is large and the specific surface area is small, which is not conducive to SF 6 At the same time, the charge distribution inside the ZrC material is very uniform, which is not conducive to the adsorption of SF 6 Molecules transfer electrons. When ZrO is selected 2 When powder is used as a carrier, the 6 There is almost no degradation effect. Only when SiC is used as a carrier can the degradation of SF be achieved. 6 Highly efficient degradation (100% degradation rate in the range of 30-110min). SiC is a commonly used abrasive due to its high hardness. After mixing with ZrC, the size of the material becomes more uniform, which is conducive to adsorption and reaction. In addition, SiC has the properties of a semiconductor, which can redistribute electrons between ZrC and SiC, and the electronic effect can be used to accelerate SF 6 Therefore, the most preferred ZrC-based catalytic material carrier is silicon carbide.
[0066] Example 5
[0067] The ZrC-based catalytic material preparation method, treatment device and treatment process of Example 1 are used, except that the treatment temperature of the tube furnace is adjusted as shown in Table 3, and the effect of the treatment temperature on the degradation efficiency is tested. The results are as follows: Figure 7 shown.
[0068] Table 3. Effect of different degradation temperatures on degradation
[0069]
[0070]
[0071] analyze:
[0072] The degradation temperature will affect the degradation effect of ZrC-based catalytic materials. At 400 °C, ZrC-based catalytic materials cannot activate SF 6 When the temperature rises to 500℃, the ZrC-based catalytic material begins to react with SF 6 reaction, at this time the maximum degradation rate is 100%, the SF per unit ZrC 6 The degradation amount reached 986.5 mL g -1 When the temperature is further increased to 600℃, SF 6 The unit degradation amount can reach 2316.7mL g -1 , the degradation life is as long as 250 minutes (the degradation rate is 100% in the degradation time of 30-240 minutes). Therefore, it is not difficult to see that temperature has a great influence on SF 6 The degradation effect of SF is greatly affected by high temperature, and the ZrC-based catalytic material is beneficial to the degradation of SF 6 Activation and degradation of molecules. For energy saving and economic considerations, the degradation temperature is preferably 500°C.
[0073] Example 6
[0074] The ZrC-based catalytic material preparation method, treatment device and treatment process of Example 1 are used, except that the selection of active centers is adjusted, as shown in Table 4, and the influence of active centers on degradation efficiency is tested. The results are as follows: Figure 8 shown.
[0075] Table 4. Effects of different active centers on degradation
[0076]
[0077] analyze:
[0078] The active centers will affect the degradation effect of SiC carrier catalytic materials.
[0079] When the active center is ZrO 2 and Zr(HPO 4 ) 2 .2H 2 O, SF per unit mass of active center 6 The degradation amount is 0, indicating that ZrO 2 and Zr(HPO 4 ) 2 .2H 2 O composite SiC after SF 6 Therefore, it is not difficult to see that the composition of the active center has an important influence on the SF 6 The composite catalytic material composed of ZrC and SiC has a great influence on the degradation effect of SF 6The activation and degradation effects of the molecules are the best. Therefore, the most preferred active center of the ZrC-based catalytic material is zirconium carbide.
[0080] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere, characterized in that: The invention uses zirconium carbide as the active site center and silicon carbide as the carrier. The zirconium carbide is dispersed on the silicon carbide, and the mass of the zirconium carbide accounts for 5-50% of the mass of the catalytic material.
2. The zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to claim 1, characterized in that: The mass of the zirconium carbide accounts for 10% of the mass of the catalytic material.
3. A method for preparing a zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere as claimed in claim 1 or 2, characterized in that: The following steps are involved: The zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere is obtained by physically mixing zirconium carbide and silicon carbide.
4. The method for preparing a zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to claim 3, characterized in that: The physical mixing method is grinding.
5. Use of the zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere as claimed in claim 1 or 2 in degrading sulfur hexafluoride.
6. A method for degrading sulfur hexafluoride using the zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere as claimed in claim 1 or 2, characterized in that: The following steps are involved: A zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere is placed in a reaction device, a mixed gas of sulfur hexafluoride and air is introduced, and a heating treatment is performed at 500-600° C. to degrade sulfur hexafluoride.
7. The method for degrading sulfur hexafluoride using a zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to claim 6, characterized in that: In the mixed gas of sulfur hexafluoride and air, the volume concentration of sulfur hexafluoride is not greater than 60 vol.%.
8. The method for degrading sulfur hexafluoride using a zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to claim 6, characterized in that: The method also includes subjecting the heated gas to treatment with a 5 mol / L sodium hydroxide solution.
9. The method for degrading sulfur hexafluoride using a zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to claim 6, characterized in that: The sulfur hexafluoride was degraded by heating at 500°C.
10. The method for degrading sulfur hexafluoride using a zirconium carbide-based catalytic material capable of degrading sulfur hexafluoride in an air atmosphere according to any one of claims 6 to 9, characterized in that: The flow rate of the mixed gas of sulfur hexafluoride and air is 10 mL / min.
Citation Information
Patent Citations
Method for high efficiency treatment of?sulfur hexafluoride (SF6) pollution gas?through electroplating sludge
CN103007736A
Silicon carbide-iron oxide composite material for decomposing sulfur hexafluoride in atmospheric environment and application thereof
CN113244939A
Catalytic material based on elemental manganese for degrading sulfur hexafluoride in air atmosphere
CN116078416A
Molybdenum dioxide-based catalytic material for degrading sulfur hexafluoride in air atmosphere
CN116474762A